Researching tourism and development in Southeast Asia: Methodological insights - Dolezal, Claudia; Trupp, Alexander *; Prasit, Leepreecha (Routledge, 2020)
Tourism for development has become an essential research field in its own right, also in Southeast Asia. Researchers and scholars within the region, but more broadly from around the world, dedicate themselves to understanding how to use tourism most efficiently as a development strategy. Much of this research is based on anthropological approaches, with field work as the prime method employed. However, very little has been said about the challenges that researchers with different positionalities encounter in the field, such as access to the field, language or working with interpreters, and power relations. This chapter therefore debates these challenges and points towards ways to address these by drawing on examples from the authors’ fieldwork in foreign and familiar fields. Examples include discussions on the above-mentioned challenges, with a specific focus on the emic versus etic perspective, also seen as the ‘insider-outsider’ debate. In doing so, the chapter demonstrates that there is no ‘ideal’ position from which to do research in the Southeast Asia. It deromanticises the idea of fieldwork at home as delivering more truthful accounts of the field and, finally, points towards the need for reflexivity in order to make our field research in Southeast Asia more robust and effective.